SISLAB - Um software de gestão de salas de aula e laboratórios - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The present work deals with the creation of a web application to manage the reservation of rooms and equipment at the Universidade do Estado do Pará, campus Santarém-PA. To solve this problem, a web system was developed to reserve laboratories (rooms) and equipment, which has the purpose of automating the management of the request for reservation of class spaces. Throughout this work, several methodological procedures were carried out, starting with an exploratory research in the educational institution that is the focus of this project, passing through the requirements definition phase through the use of software engineering techniques such as documents and diagrams. To perform the software coding it was used the Laravel framework with the programming language PHP. With the product developed, a questionnaire was applied with the purpose of evaluating the effectiveness of the software and after analyzing the results obtained in the questionnaires it was noticed that the software meets what was initially planned. Solving problems encountered by the administrative technicians of UEPA in the management of laboratory and equipment reservation, avoiding conflict of requests and storing in a database all the necessary information for the management of the application. Another important point regarding the developed software is the possibility of it being used by other institutions, since it can be distributed for free to the community in general.
Keywords: Reservas; Laravel; PHP; MVC; Engenharia de Software; CNPQ:: CIÊNCIAS EXATAS E DA TERRA